La publicidad online en el comercio electrónico y su influencia en las actitudes de los usuarios milenials en Lima Metropolitana - Palomino Cruz, Eduardo Saidt (2022)
Millennials are part of the first generation to grow at the same rate as digital media; the generation whose year of birth is between 1979 and 1994, has as its main characteristic that they grew up technologically connected, concerned about environmental and social issues; This generation always seeks their well-being, whether at work or in their daily lives, they want to live in the moment and do not prioritize economic possessions. Currently it is one of the most important objectives for marketing, since it is a generation with a lot of influence and digital interaction. The present investigation seeks to know the generation that grew up with the internet and its relationship with online advertising, created in order to promote goods and services through digital channels to achieve a greater reach, as well as create brands, interact with customers and personalize their services. The main objective of this research is to measure the attitudes of millennial users in metropolitan Lima towards online advertising, which due to the situation in the years 2020 - 2021, was increased exorbitantly by the need to people to acquire products without leaving their homes, this investigation could help other students to analyze online advertising in a pandemic situation.